Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1103/physrevb.42.7981
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order and electronic phase diagrams of electron-doped copper oxide materials

Abstract: We report muon spin relaxation and rotation measurements on sintered ceramic samples of Nd2 "Ce"Cu04y and a large single crystal of Nd2Cu04 y. We find an electronic phase diagram that is quite similar to that of hole-doped superconductors such as La2 "Sr"Cu04y although the doping of electrons into the system is less efficient in destroying the static moments on the copper ions. Static magnetic order appears in Nd2Cu04~below about 250 K; two spin reorientations are seen at T=75 and 35 K, providing information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(55 citation statements)
references
References 27 publications
4
51
0
Order By: Relevance
“…In these materials commensurate (π, π) spin density wave order has been detected by muon spin rotation 5 and neutron scattering measurements. 6,7 The order exists over a wide range of dopings and vanishes at a critical doping x c near the "optimal" doping x = 0.16.…”
Section: Introductionmentioning
confidence: 99%
“…In these materials commensurate (π, π) spin density wave order has been detected by muon spin rotation 5 and neutron scattering measurements. 6,7 The order exists over a wide range of dopings and vanishes at a critical doping x c near the "optimal" doping x = 0.16.…”
Section: Introductionmentioning
confidence: 99%
“…Recent low temperature normal state Hall effect measurements [8] on Pr 2−x Ce x CuO 4−δ (PCCO) show a sharp kink of the Hall coefficient at a critical doping x =0.16, which suggests a quantum phase transition (QPT) at this doping. Early µSR measurements found that the AFM phase starts at x =0 and persists up to, or into, the SC dome [9]. Neutron scattering experiments [10] show an AFM phase above critical field in an optimally doped n-type cuprates, but no such phase on the overdoped side.…”
mentioning
confidence: 99%
“…4, thermally ac- Black squares and dash line are the controversial AFM transition temperature from Ref. [9,10] and Ref. [14] respectively.…”
mentioning
confidence: 99%
“…This problem is a central issue not only in HTSCs but also in other exotic superconductors such as heavy-fermion and organic-salt superconductors. In the phase diagram of electron-doped cuprates, the AF and SC phases are adjacent to each other or somewhat overlap at the boundary, in contrast to the hole-doped case where the two phases are well separated [1]. The proximity or overlapping between the AF and SC phases in the electron-doped cuprates yields a good opportunity for studying the interplay between the AF interaction and the superconductivity [2,3,4,5].…”
mentioning
confidence: 99%